The Glossa Ordinaria on Romans - Woodward, Michael S. (Book collections on Project MUSE., 2011)
The Gloss on Romans is a collection of sources from many periods and places, which accounts for its inconsistencies. And this is what gives the Gloss much of its charm ... The twelfth century was an age of gathering sources and commentaries, in theology (Lombard's Sentences), canon law (Gratian's Decretum), and biblical studies (the Glossa ordinaria). Education began to flourish into what would become universities, where the master's role was to elucidate traditional, authoritative texts. And chief among these was the Bible, not standing alone but with the accompanying Gloss." - from the introduction.